(untitled) - Stone, Amey (New York, 2002)
Sanford Weill, known as a ruthless deal-maker and the creator of successful businesses like Citigroup, has revolutionized the banking world and become a legend on par with Warren Buffett and Jack Welch. Stone and Brewster, both journalists and editors of online business publications, discuss Weill's successful strategies and tactics through case studies and anecdotes from his professional and personal life. They cover his entire career, including his violation of federal law when in 1992 he merged banking and insurance businesses. He later lobbied the President and Congress to deregulate the financial services industry. In a power struggle in 2000, he ousted his co-CEO, John Reed, at Citigroup. The chronicle of his ascent to executive greatness demonstrates the opportunities he seized that others could not or would not dare to take in a world of financial intrigue and globalization. This candid business biography does not critique Weill's more questionable actions but instead serves to demonstrate the need for determination, self-confidence, and strong management skills to become an outstanding CEO in today's global business world. Recommended for business collections.
Keywords: Bankers,Chủ ngân hàng; Biography,Tiểu sử; United States,Hoa Kỳ